Evaluation of a zinc chelate on clinical swine dysentery under field conditions - Frédéric Vangroenweghe; Liesbeth Allais; Ellen Van Driessche; Robbert van Berkel; Gerwen Lammers; Olivier Thas (Porcine Health Management, 2020)
Abstract Background Brachyspira hyodysenteriae is the primary cause of swine dysentery, characterized by bloody to mucoid diarrhea due to mucohaemorhagic colitis in pigs and primarily affects pigs during the grow/finishing stage. Control and prevention of B. hyodysenteriae consists of administration of antimicrobial drugs, besides management and adapted feeding strategies. A worldwide re-emergence of the disease has recently been reported with an increasing number of isolates demonstrating decreased susceptibility to several crucially important antimicrobials in the control of swine dysentery. A novel non-antibiotic zinc chelate has been reported to demonstrate positive effects on fecal quality and consistency, general clinical signs, average daily weight gain and B. hyodysenteriae excretion during and after a 6-day oral treatment. The objective of the present study was to evaluate the zinc chelate (Intra Dysovinol® 499 mg/ml (ID); Elanco) on naturally occurring swine dysentery due to B. hyodysenteriae under field conditions in the Netherlands. Results Oral administration of zinc chelate resulted in improvement of general clinical signs from 3 days onwards in the ID-treated group combined with a significantly better total fecal score at 14 days post-treatment. Overall, average daily weight gain was better in the ID-treated group over the entire study period (0–14 days) and during the 8 days following the end of ID-treatment. A significant reduction (4.48 vs. 0.63 log10 cfu/g feces; ID-treated vs. control) in B. hyodysenteriae excretion was observed during the 6-day treatment period with a high percentage of animals (58.3 vs. 12.3%; ID-treated vs. control) with no excretion of B. hyodysenteriae from their feces. No additional antimicrobial treatment was needed in the ID-treated group, whereas 35% of the pigs in the control group were treated with an antibiotic at least once. No mortality occurred in both groups. No adverse events were reported during and following the ID-treatment. Conclusions Zinc chelate – administered as a Zn-Na2-EDTA complex – is a non-antibiotic treatment for swine dysentery that reduces B. hyodysenteriae shedding with 4.48 log10 cfu/g feces within its 6-day treatment while improving general clinical signs (90.0 vs. 73.6% animals with normal score) and total fecal score within 2–4 days following administration in naturally infected pigs. The positive effects of ID treatment remain for at least 8 days after cessation of oral ID therapy. Pigs remaining in a highly contaminated environment may be re-infected following the end of ID treatment, however, this is not different to standard antimicrobial therapy. Therefore, control of swine dysentery should combine an efficacious treatment with additional management practices to reduce the environmental infection pressure in order to limit re-infection as much as possible. The ID treatment resulted in a higher growth rate and improved general health, whereas no mortality was observed and no additional therapeutic treatments were necessary in contrast to the control pigs.